2005
DOI: 10.4319/lo.2005.50.1.0237
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of the cyanobacterial pigment phycocyanin in turbid inland water

Abstract: The pigment phycocyanin (PC) is a marker for cyanobacterial presence in eutrophic inland water. We present a reflectance band-ratio algorithm for retrieval of cyanobacterial PC. The model conforms to the band settings of the Medium Resolution Imaging Spectrometer. The parameters of the algorithm were optimized using reflectance and absorption data from two highly eutrophic lakes. Using measured specific absorption coefficients for PC [a (620)] * pc for every sample, the error in the predicted PC concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
404
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(422 citation statements)
references
References 32 publications
14
404
1
3
Order By: Relevance
“…According to Simis et al (2005), 6 ml of phosphate buffer was enough to achieve maximum extraction in the concentration range of 2−50 µg l −1 . However, our study aimed to clarify whether this method was useful not only in oligotrophic lakes, but in hypertrophic waters dominated by blue-green algae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Simis et al (2005), 6 ml of phosphate buffer was enough to achieve maximum extraction in the concentration range of 2−50 µg l −1 . However, our study aimed to clarify whether this method was useful not only in oligotrophic lakes, but in hypertrophic waters dominated by blue-green algae.…”
Section: Discussionmentioning
confidence: 99%
“…Seppälä et al, 2007), sensitive fluorometric techniques (Gregor & Maršálek, 2005), remote sensing (e.g. Simis et al, 2005;Hunter et al, 2008aHunter et al, , 2008b, and in vitro extraction methods have all been used for cyanobacterial quantification (Sarada et al, 1999). A number of studies have been published on phycocyanin extraction methods and their comparative analyses (Zhu et al, 2007;Lawrenz et al, 2011;Zimba, 2012); however there is no standard protocol for the maximal extraction of phycocyanin from cyanobacteria cells.…”
Section: Introductionmentioning
confidence: 99%
“…There are ongoing efforts to refine the monitoring of HABs into determining the dominant taxa of the bloom. Simis et al [5] used the strong absorption of phycocyanin as a bioindicator of cyanobacteria dominated blooms. Kutser et al [6] clearly showed the placement of specific optical wavelength bands on the multi-spectral sensor MERIS (medium resolution imaging spectrometer) mounted on ESA's ENVISAT enables routine monitoring of phytoplankton blooms and identifying if the blooms are cyanobacteria dominated.…”
Section: Introductionmentioning
confidence: 99%
“…The advances in optical sensor design, bio-optical algorithms and validation methods have also supported the retrieval of a wide range of new water quality parameters (e.g. phycocyanin, particulate organic carbon, phytoplankton size distribution) (Simis et al, 2005;Nair et al, 2008;Allison et al, 2010;Ciotti & Bricaud 2010;Hunter et al, 2010;Brewin et al, 2011;Sun et al, 2013).…”
Section: Figurementioning
confidence: 99%